The effect of shoulder injury prevention program on glenohumeral range of motion and upper extremity performance in adolescent throwers: A pilot study - Cobanoglu, G.; Aka, H.; Guzel, N. A. (Baltic Journal of Health and Physical Activity, 2021)
Background: The Oslo Sports Trauma Research Center (OSTRC) Shoulder Injury Prevention Program is an exercise program developed to increase the internal rotation (IR) range of motion (ROM), external rotator muscle strength and scapular muscle strength and to improve kinetic chain involvement and thoracic mobility. The purpose of this study is to investigate the effect of this program on glenohumeral ROM and upper extremity functional performance in adolescent throwers. Material and Methods: Ten adolescent throwers (discus, shot put and javelin throwers) were involved in the study. The OSTRC Shoulder Injury Prevention Program was applied three times a week for 8 weeks as a handball warm-up. Glenohumeral IR and external rotation (ER) ROM were evaluated with a goniometer. The Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) was used to evaluate the upper extremity functional performance. Results: It was found that there was a statistically significant difference in the dominant side IR ROM and CKCUEST between the pre-test and post-test (p<0.05); however, there was no difference in terms of other parameters (p>0.05). Conclusions: This study shows that the glenohumeral IR ROM and upper extremity functional performance increases after the 8-week OSTRC Shoulder Injury Prevention Program. For these purposes, physiotherapists and trainers can include this program in their training programs.